BASIC PARAMETERS OF TRADE DEFICIT IN PAKISTAN - Allah Bux Lakhan; Zulfiqar Ali Keeryo; Jazib Mumtaz (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
In this study the co-integration and error correction mechanism (ECM) are used along with granger-causality for Pakistan. In this analysis, the environment of export and import is examined for to trace the level of trade deficit in Pakistan. As suggested from data the share of imports is higher than the share of exports which resulted in the persistent trade deficit in Pakistan. This research tells the basic parameters which affected the balance of trade directly or indirectly. The results of study suggest that Pakistan has many opportunities to work for international competitiveness and to come out from the problem of trade deficit. The study also relates that Pakistan can control or lessen the trade deficit by focusing on some specific areas.